Preferential segregation involving a knobless chromossome in maize - Saraiva, Luiz Sérgio (Revista Ceres, 2025)
A translocated chromosome (9B) arose in which all of the distal heterochromatin of the B chromosome was attached to the short arm of chromosome 9 in maize.